Developing Interactive Quizizz-Based Learning Media to Enhance Arabic Vocabulary and Grammar Skill - Muthongah, Binti Mar’atul; Saidah, Ratna; Hartanto, Eko Budi (Al-Wazan: Journal of Arabic Education, 2025)
Media plays a crucial role in the learning process, and the advancement of technology has introduced various innovative tools that can enhance student engagement and learning outcomes. However, the integration of technology-based media in Arabic language instruction remains limited in several educational institutions, including MTsN 3 Kediri, particularly among eighth-grade students. This study aims to develop and describe the use of Quizizz interactive learning media in Arabic language learning to improve students’ mastery of mufradāt (vocabulary) and qawāʿid (grammar). Employing a Research and Development (R&D) design with the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—this research was conducted from January to February in class VIII-B, involving 36 students. The study used a one-group pretest–posttest design to evaluate the effectiveness of the developed media. Validation results from media, material, and learning experts yielded an average score of 89%, categorized as very feasible, while student responses indicated 88% satisfaction, classified as very interesting. Furthermore, the pretest mean score of 60 increased to 87 in the posttest, with a t-test result of tcount = 13.26 > ttable = 1.67 (α = 0.05), indicating a significant improvement in learning outcomes. These findings confirm that Quizizz-based interactive media effectively enhance students’ Arabic vocabulary and grammar skills while promoting engaging, technology-oriented learning experiences aligned with the needs of the digital generation.